Determinants and Management of Make-and-Buy An Extension to Transaction Cost Economics - Krzeminska, Anna (Beiträge zur betriebswirtschaftlichen Forschung, 2009)
While making and buying are usually regarded as being mutually exclusive in extant theory, in reality, making-and-buying is employed in various contexts, such as industrial manufacturing, the media, and clinical trials. After assessing transaction cost economics as the most important theory of the make vs. buy decision, Anna Krzeminska develops an extension to the TCE framework which spotlights uncertainty as a main explanatory variable. This approach not only allows distinguishing different types of make-and-buy but also enables an explanation of determinants, management mechanisms, and performance implications of each make-and-buy type separately. Empirical analysis with data from the German automotive industry shows predominant support for the hypotheses. Thus, this work contributes to a better understanding of the categorization of economic institutions.